When Hormone Defects Cannot Explain It: Malformative Disorders of Sex Development - Grinspon, Romina (2014)
The birth of a baby with malformations of the genitalia urges medical action. Even in cases where the condition is not life-threatening, the identification of the external genitalia as male or female is emotionally essential for the family, and genital malformations represent one of the most stressful situations around a newborn. The female or male configuration of the genitalia normally evolves during fetal life according to the genetic, gonadal, and hormonal sex. Disorders of sex development occur when male hormone (androgens and anti-Müllerian hormone) secretion or action is insufficient in the 46,XY fetus or when there is an androgen excess in the 46,XX fetus. However, sex hormone defects during fetal development cannot explain all congenital malformations of the reproductive tract. This review is focused on those congenital conditions in which gonadal function and sex hormone target organ sensitivity are normal and, therefore, not responsible for the genital malformation. Furthermore, because the reproductive and urinary systems share many common pathways in embryo-fetal development, conditions associating urogenital malformations are discussed.